MAKNA IBADAH KRISTEN BERDASARKAN ROMA 12:1-2 BAGI PEMBINAAN SPIRITUALITAS REMAJA DI GMIT REHOBOT RININ - AMARASI BARAT - Nobrihas, Anri Yufli; Mudak, Sherly; Rasi, Anre (Jurnal Arrabona, 2025)
This article discusses the challenges faced by teenagers in the context of worship at GMIT Rehobot, Rinin, West Amarasi, regarding the phenomenon of teenagers' inactivity in worship, which is often caused by emotional instability and feelings, as well as a lack of deep understanding of the meaning of worship. This research uses a qualitative method that emphasizes the social reality that is built and the values contained in the teenagers' worship experience. The purpose of the study was to identify problems related to teenagers' worship and provide recommendations to increase their participation in worship activities. The results showed that teenagers tend to attend church only to socialize, so a more holistic approach is needed in fostering their spirituality. The study recommends the development of programs that can increase teenagers' understanding and involvement in worship, as well as emphasizing the importance of worship as a means of sustainable spiritual growth.